Characteristics and Regulating Roles of Wheat TaHsfA2-13 in Abiotic Stresses - Meng, Xiangzhao; Zhao, Baihui; Li, Mingyue; Liu, Ran; Ren, Qianqian; Li, Guoliang; Guo, Xiulin (Frontiers in Plant Science, 2022)
Heat shock transcription factor (Hsf) exists widely in eukaryotes and responds to various abiotic stresses by regulating the expression of downstream transcription factors, functional enzymes, and molecular chaperones. In this study, TaHsfA2-13, a heat shock transcription factor belonging to A2 subclass, was cloned from wheat (Triticum aestivum) and its function was analyzed. TaHsfA2-13 encodes a protein containing 368 amino acids and has the basic characteristics of Hsfs. Multiple sequence alignment analysis showed that TaHsfA2-13 protein had the highest similarity with TdHsfA2c-like protein from Triticum dicoccoides, which reached 100%. The analysis of tissue expression characteristics revealed that TaHsfA2-13 was highly expressed in root, shoot, and leaf during the seedling stage of wheat. The expression of TaHsfA2-13 could be upregulated by heat stress, low temperature, H2O2, mannitol, salinity and multiple phytohormones. The TaHsfA2-13 protein was located in the nucleus under the normal growth conditions and showed a transcriptional activation activity in yeast. Further studies found that overexpression of TaHsfA2-13 in Arabidopsis thaliana Col-0 or athsfa2 mutant results in improved tolerance to heat stress, H2O2, SA and mannitol by regulating the expression of multiple heat shock protein (Hsp) genes. In summary, our study identified TaHsfA2-13 from wheat, revealed its regulatory function in varieties of abiotic stresses, and will provide a new target gene to improve stress tolerance for wheat breeding.